Prediction Model for Peak Expiratory Flow Rate in Rural Indian Girls - Dr.Sudeep Kale; Dr. Mangala Deshpande; Dr.Sandip Chaudhari (International Journal of Pharma and Bio Sciences, 2021)
Peak Expiratory flow rate (PEFR) is an easy method to evaluate the airway & lung function. The need for normative data for PEFR is expressed by many researchers. The American thoracic society (ATS) & European Respiratory Society (ERS) has recommended to establishing local reference values for PEFR & other lung function parameters. The research to establish reference data for PEFR in India is a relatively ignored aspect. The reference data is available for adult population. In a paediatric population, the data is available for South Indian, North Indian urban boys. The rural population is not studied well. The current study was designed to understand the relation of PEFR with age, height, weight, body mass index (BMI), body surface area (BSA) & to establish a reference prediction equation in rural girls living in Maharashtra. PEFR was taken in 6-15 years aged 262 school going normal healthy rural girls from Bansarola village, District Beed, Maharashtra. The height, weight, age, BMI & BSA was measured. The correlation was done by Pearson’s correlation coefficient & regression analysis was done for predicting the statistical models. Correlation was significant at the 0.01 level (2-tailed). Diagnostic F value of model was 75.892. PEFR was correlated with age, height, weight, BMI & BSA. The weight & BSA explained maximum variation in data whereas BMI explained the least variation. PEFR values in rural girls were lower than urban boys & girls.In conclusion there are variation in PEFR amongst urban & rural girls which highlights the need to establish local data & prediction equations for PEFR.